'Better off with Labour'? Fiscal policy, electoral strategy and the road to John Smith's shadow budget, 1979–92. Issue 267 (3rd December 2021) - Sloman, Peter
Abstract: The failure of John Smith's 'Shadow Budget' to deliver a Labour victory in the 1992 general election has taken on a mythical status in narratives around the development of New Labour. This article sets the episode in a larger context by examining the development of Labour's fiscal policies in opposition after 1979, in the face of rising inequality, public-sector austerity, and regressive tax reforms. It traces how successive election defeats drove a process of political learning, which came to revolve around the effort to reassure floating voters that a Labour government could control tax, spending and borrowing. The 1992 defeat seemed to demonstrate the difficulty of winning support for redistribution in the face of 'tax bombshell' attacks, and so paved the way for the more cautious and incremental fiscal politics of Gordon Brown and New Labour.